Assessing ethical and social issues of transtelephonic electrocardiography (TTEGG) in Chile - Eugenia Lamas; Silvia Miguel; Holger Muehlan; Silke Schmidt; Rodrigo A. Salinas (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2014)
The aim of this study was to focus on the ethical and social issues derived from the implementation of transtelephonic electrocardiography (TTECG) in the public healthcare sector in Chile, studying patients and healthcare providers' acceptance and expectations concerning: (a) TTECG effectiveness and safety; and (b) data protection issues, such as confidentiality, privacy and security. For this purpose, we developed two psychosocial surveys; the first was addressed to patients receiving transtelephonic electrocardiogram (either in the emergency services of hospitals or in distant primary care services) and the second one aimed at healthcare providers involved in either administering and/or interpreting it. Results included: (a) major acceptability of TTECG in terms of safety and security; (b) privacy and confidentiality of the patients were considered to be well protected; and (c) the patient-doctor relationship was not affected by this device.